2009
DOI: 10.1038/hr.2009.137
|View full text |Cite
|
Sign up to set email alerts
|

Non-dipping pattern in ambulatory blood pressure monitoring is associated with metabolic abnormalities in a random sample of middle-aged subjects

Abstract: A reduction in the blood pressure decline at night (o10% from daytime systolic blood pressure (SBP)) during 24-h ambulatory blood pressure monitoring (ABPM) ('non-dipping pattern') is associated with cardiovascular morbidity. Our aim was to evaluate whether ABPM characteristics are associated with metabolic abnormalities in subjects without known hypertension or type 2 diabetes mellitus (T2DM). This is a cross-sectional population-based study on middle-aged subjects (n¼462). Two distinct definitions of metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…20 These pathological modifications in risk factors may be reflected in the tendency for nondipping subjects to develop atherosclerosis. Recently it has been documented, that a higher BP variability during night-time independently correlated with a higher IMT.…”
Section: Discussionmentioning
confidence: 99%
“…20 These pathological modifications in risk factors may be reflected in the tendency for nondipping subjects to develop atherosclerosis. Recently it has been documented, that a higher BP variability during night-time independently correlated with a higher IMT.…”
Section: Discussionmentioning
confidence: 99%
“…There are other reports supporting the relationship between MS and a nondipping pattern [24, 2830]. Additionally, nondipping status has been shown to be an independent predictor of glucose tolerance and several other metabolic abnormalities [31]. In contrast, other studies reported no difference in the ambulatory BP patterns between patients with and those without MS. With regard to the components of MS, glucose and abdominal obesity were two important components, but the number of components itself was also a determinant of the nondipping pattern.…”
Section: Metabolic Syndrome and Circadian Rhythm Of Bpmentioning
confidence: 97%
“…Day-time and night-time blood pressure values and their changes due to treatment are related to each other [15], but the prognostic value of night-time blood pressure has been found superior [16]. Moreover, patients with a non-dipper circadian pattern of BP are at higher risk of micro- and macrovascular complications, such as cerebrovascular and cardiovascular complications, than individuals with a dipper circadian rhythm [17, 18]. Non-dipping of nocturnal BP seems to be a determinant of cardiac remodelling and LV diastolic dysfunction (LVDD) and may result in a cardiovascular risk independent of the increase in LVM in both hypertonic patients and in normotensives [19].…”
Section: Introductionmentioning
confidence: 99%